EMPOWERING ADOLESCENTS AS STUNTING PREVENTION AGENTS: SWABANTU PROGRAM THROUGH ANTHROPOMETRIC SCREENING TRAINING AND PRACTICE - Yumni, Hilmi; Minarti, Minarti; Fadilah, Nikmatul; Harnani, Baiq Dewi (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
Stunting is a chronic nutritional problem that remains a public health challenge, including in Sidoarjo Regency. Adolescents play a strategic role as agents of change in stunting prevention through information dissemination and direct involvement in nutritional screening. This community service activity aims to empower adolescents through an educational and participatory approach integrated into the Swabantu Program. The activities include increasing knowledge, training on anthropometric measurement skills, and field practice with the guidance of healthcare personnel and cadres. The participants comprised 40 adolescents, health cadres, and 10 community leaders. The activities were conducted in four sessions, which included: providing material on stunting and adolescent reproductive health; training in the measurement skills of height, weight, and upper arm circumference; conducting measurements on eight toddlers; and presenting and interpreting the results. The implementation methods included interactive lectures, question and answer, group discussions, skill stations, field practice, and evaluation using pre-tests and post-tests. Learning media included educational modules, early detection identification sheets, and measuring tools such as microtoise, digital scales, and upper arm circumference tapes. The pre-test and post-test instruments were validated by experts and analyzed descriptively, with paired t-tests used to measure intervention effectiveness. The results showed an average knowledge score increase from 58.2 to 78.6 (p < 0.05), with 100% of participants performing anthropometric measurements correctly. Qualitative data were analyzed thematically through observation and discussions. Assessments of the eight toddlers showed that all had normal height, 62.5% were underweight, and 87.5% had normal upper arm circumference. Challenges during implementation included limited field practice time, variation in participant understanding, and coordination with toddler families. Nevertheless, this activity successfully enhanced adolescents' knowledge, skills, and potential as community agents in stunting prevention.